Find Cancer Early: Evaluation of a Community Education Campaign to Increase Awareness of Cancer Signs and Symptoms in People in Regional Western Australians - Croager, Emma Jane; Gray, Victoria; Pratt, Iain Stephen; Slevin, Terry; Pettigrew, Simone; Holman, C. D’arcy; Bulsara, Max; Emery, Jon (Frontiers in Public Health, 2018)
Introduction Cancer outcomes for people living in rural and remote areas are worse than for those living in urban areas. Although access to and quality of cancer treatment are important determinants of outcomes, delayed presentation has been observed in rural patients. Methods Formative research with people from rural Western Australia (WA) led to the Find Cancer Early campaign (FCE). FCE was delivered in three regions of WA, with two other regions acting as controls. Staff delivered the campaign using a community engagement approach, including promotion in local media. Television communications were not used to minimize contamination into the control regions. The campaign evaluation was undertaken at 20 months via a Computer Assisted Telephone Interviewing (CATI) survey comparing campaign and control regions. The primary outcome variable was knowledge of cancer signs and symptoms. Results Recognition and recall of FCE, and symptom knowledge were higher in the campaign regions. More than a quarter of those who were aware of the campaign reported seeing the GP as a result of their exposure. Conclusions Despite limited use of mass media, FCE successfully improved knowledge of cancer symptoms and possibly led to changes in behavior. Social marketing campaigns using community development can raise awareness and knowledge of a health issue in the absence of television advertising.